Learn Flutter and Dart to build iOS and Android apps (Packt Publishing, 2018)
"This course will teach you Flutter and Dart from scratch. With Flutter, you'll be able to write code only once and ship your apps both to the Apple AppStore and Google Play. Use Google's Material Design to build beautiful yet fully customizable apps in no time with almost zero effort. You can use the rich widget suite Flutter provides to add common UI elements such as buttons, switches, forms, toolbars, lists, and more--or simply build your own widgets--Flutter makes that a breeze too. You're interested in building real native mobile apps for the two most popular mobile platforms - iOS and Android. You want to explore the full set of features Flutter offers. Don't want to spend hours learning two completely different languages."--Resource description page